RELEVANSI KURIKULUM MERDEKA BELAJAR-KAMPUS MERDEKA (MBKM) DENGAN ERA SOCIETY 5.0 - Mutaqin, Ade Zaenul (HASBUNA : Jurnal Pendidikan Islam, 2024)
The Society 5.0 era is an era that requires humans to be able to elaborate on technology, without mortgaging humanity. This era was initiated by the Japanese government which also had an impact on the world of education. The impact on the world of education in the end is that students are required to improve various skills, be it soft skills, hard skills or power skills. To answer these challenges, the government, through the Minister of Education and Culture, launched the Independent Learning-Free Campus program, which was then abbreviated as MBKM. This program is a learning concept that encourages students to think critically and gives students freedom in learning. This article aims to examine the relevance of the Independent Learning-Free Campus program in the Era of Society 5.0, especially in higher education. This study was carried out with a qualitative approach and used a library study by reviewing literature that was appropriate to the topic of discussion. The results of the study conducted show that the Merdeka Belajar-Kampus Merdeka program can encourage students to become superior human beings, clever in the academic field and have soft skills as well as hard skills and power skills that are relevant to the era of society 5.0.